2003
DOI: 10.1111/j.1572-0241.2003.07666.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endoscopic surveillance of patients with Barrett's esophagus. incidence of dysplasia and adenocarcinoma: a prospective study

Abstract: The incidence of AC in BE is low, confirming recent data from the literature reporting an overestimation of cancer risk in these patients. In our patient cohort, surveillance involved a large expenditure of effort but did not prevent any cancer deaths. The benefit of surveillance remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(72 citation statements)
references
References 58 publications
1
69
1
1
Order By: Relevance
“…However, the natural history of LGD is not well characterized, with rates of progression to HGD or EAC ranging from 10 to 30%, as well as frequent regression to BE (Hameeteman et al, 1989;Weston et al, 1997;O'Connor et al, 1999;Weston et al, 1999Weston et al, , 2001Skacel et al, 2000;Conio et al, 2003). Moreover, histological classification of dysplasia, especially LGD, has high interobserver variability (Alikhan et al, 1999;Montgomery et al, 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…However, the natural history of LGD is not well characterized, with rates of progression to HGD or EAC ranging from 10 to 30%, as well as frequent regression to BE (Hameeteman et al, 1989;Weston et al, 1997;O'Connor et al, 1999;Weston et al, 1999Weston et al, , 2001Skacel et al, 2000;Conio et al, 2003). Moreover, histological classification of dysplasia, especially LGD, has high interobserver variability (Alikhan et al, 1999;Montgomery et al, 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…32 The prevalence of BE was lower in women than in men (Table). 7,19,[40][41][42][43][44][45][46][47][48][49][50][51] A systematic review after analyzing the PubMed database between 1997 and 2011 has shown that the prevalence of BE was lower in women than in men (28 out of 10 337, range 0.03-4.6% vs 70 out of 12 463, range 0.08-8.2%).…”
Section: Prevalence Of Barrett's Esophagusmentioning
confidence: 99%
“…In addition, the diagnosis is often elusive and not confirmed with repeat endoscopy and biopsies [10,11]. In part, this may be due to the high degree of interobserver variability in establishing the diagnosis of low-grade dysplasia, and the variable biopsy sampling protocols by which these patients are followed.…”
mentioning
confidence: 99%